2009
DOI: 10.1007/s00256-009-0738-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of the hands and feet for rheumatological disorders: influence on clinical diagnostic confidence and patient management

Abstract: Ultrasound of the hands and/or feet significantly influenced the rheumatologists' diagnostic confidence in specific clinical findings and management plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 13 publications
0
24
0
1
Order By: Relevance
“…Three of these studies examined the hand joints (wrist, metacarpophalangeal and proximal interphalangeal joints), but none compared sites 711. One study showed that ultrasound synovitis improved the certainty of RA diagnosis from 42.0% to 53.2% (p 0.17),7 and another described how synovitis seen with ultrasound helped confirm (65.2%) or change the diagnosis (11.1%); ultrasound was superior to clinical examination in 75% of patients 8.…”
Section: Resultsmentioning
confidence: 99%
“…Three of these studies examined the hand joints (wrist, metacarpophalangeal and proximal interphalangeal joints), but none compared sites 711. One study showed that ultrasound synovitis improved the certainty of RA diagnosis from 42.0% to 53.2% (p 0.17),7 and another described how synovitis seen with ultrasound helped confirm (65.2%) or change the diagnosis (11.1%); ultrasound was superior to clinical examination in 75% of patients 8.…”
Section: Resultsmentioning
confidence: 99%
“…When US was added to clinical findings, the diagnostic confidence in differentiating OA from inflammatory arthritis significantly increased 2. Due to the absence of strong evidence supporting the use of different imaging modalities at different anatomical sites, the systematic use of imaging in the diagnostic process was not recommended in cases with typical clinical presentation.…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective controlled observational study, Matsos et al reported a significant increase in confidence by rheumatologists using US to diagnose synovitis, tenosynovitis, erosions and enthesitis within the feet of 62 patients [45]. The inferences from these findings suggest good clinical utility for the use of US in assisting the diagnosis of foot pathology and ensuring appropriate foot structures are injected/treated.…”
Section: Current Evidence For Use Of Us To Detect Foot Pathology In Ramentioning
confidence: 88%
“…The inferences from these findings suggest good clinical utility for the use of US in assisting the diagnosis of foot pathology and ensuring appropriate foot structures are injected/treated. However, it should be noted that with only two study rheumatologists, the external validity of their findings may be limited [45].…”
Section: Current Evidence For Use Of Us To Detect Foot Pathology In Ramentioning
confidence: 99%